Relationship between attachment style, socio-demographic factors and alcohol abuse - Paulina Bronst; Klaudia Kister; Anna Szabrańska; Natalia Rektor; Julia Czechowska; Jakub Laskowski; Magdalena Mazur; Monika Zach-Źródlak; Lidia Rosa; Aleksandra Małolepsza (Kazimierz Wielki University, 2023)
Introduction and purpose Alcohol addiction is a major problem that affects both the affected individual and their immediate surroundings. The State Agency for Solving Alcohol Problems (PARPA) estimates that approximately 900,000 people in Poland are addicted to alcohol, and harmful drinking affects an even larger number of residents. Attachment style is a pattern of establishing relationships which derives from childhood. The aim of study is to assess the propensity alcohol abuse depending on attachment style and socio-demographic factors. Materials and methods Research material has been carried out by diagnostic survey method. The analysis has been conducted on the basis of data collected with a questionnaire designed by the author consisting of demographics and major part- updated Attachment Style IDR Labs Test (IDRLRAS) and Michigan Alcoholism Screening Test (MAST). The study involved 327 participants, 6 questionnaires have been rejected due to incorrectly filled form. All of the participants gave their informed consent for the research. The inclusion criterion was the age of above 18. The research has been conducted between 07.06.23 and 28.06.23. Results and conclusions In the group of studied individuals, there are relationships between attachment style, socio-demographic factors, and predisposition to alcohol addiction. It is important to conduct a larger number of studies on a more diverse research group in order to obtain the data needed to confirm the results discussed in the later part of the paper.